Kerusakan Partikel Pangan Selama Dalam Pemompaan - Budi Rahardjo; Sudhir K. Sastry (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1994)
Damage to food particles during pumping was studied using potatoes shaped into cubes, cylinders and spheres. The variables studied included particle size ratio, density ratio, particle volumetric fraction, Reynolds number, Froude number, and Euler number. The results indicated that the particle size ratio, the Reynolds number, the Froude number, and the Euler number significantly affected the broken particle fraction. The effect of the volumetric fraction of particle was found to be significant when it was less than 0.01. The density ratio and the flow direction of liquid did not have significant effects on the particle fraction